If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 7 + 4x + -1 = 90 Reorder the terms: 7 + -1 + 8x + 4x = 90 Combine like terms: 7 + -1 = 6 6 + 8x + 4x = 90 Combine like terms: 8x + 4x = 12x 6 + 12x = 90 Solving 6 + 12x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 12x = 90 + -6 Combine like terms: 6 + -6 = 0 0 + 12x = 90 + -6 12x = 90 + -6 Combine like terms: 90 + -6 = 84 12x = 84 Divide each side by '12'. x = 7 Simplifying x = 7
| 2(8a-5)=4a | | 2/9-1/2 | | 6(3x+2y)-3y= | | x+17=3x-4 | | 1.5(4a+100b)=c | | -7(x+1)-x-8=-8(x+5)+25 | | .15*45+35= | | 100+10(25)=15(25) | | -1/6x-3=-5/3x | | 6a-a+7-5= | | 3q+2(5-q)= | | 2n-6=n+4 | | -28+8x=-8(3x-1)-4 | | (X+2)3=128 | | 4(5-5x)=60 | | 7x-3=6x-9 | | 16-32/4 | | .55*12+17= | | 7w-5=-6+2(w-7) | | 34-4b=18 | | 10-3v=49 | | 5-2d+4d-7+w= | | -2-3(1-x)=(-2x+7) | | 2m+(-3)=24 | | 5x-3+9x=4x-9 | | 2/3-1=20 | | 3n+19=28 | | -8h-64h=-2(7h+3)+2h | | -4x+7x-8=3(x-3)-5 | | 8m+28=24 | | 9+4.5= | | .15*12+35= |